About entrepreneurs. On the basis of the thought of Veblen and Sombart (in Polish) (Diametros, 2011)
The goal of this article is to formulate a conception of the entrepreneur based on the branches of social theory that are related to the material circumstances of life in society: property, poverty, wealth, work and action. The article outlines the impact of Thorstein Veblen’s and Werner Sombart’s thought on the modern theory of the enterprise. Author advances the thesis that independence making a living constitutes the beginning of the enterprise, which is the foundation of modern capitalism. The modern capitalist enterprise frees itself from its founder, and thus cannot be limited by him.
Keywords: Veblen; Sombart; entrepreneur; work; craftsman; capitalism